Design and analysis of triple-band SIW antenna for K-Band and Ka-Band applications - Alam, Md Mahabub; Ahmad Afif, Mohd Faudzi; Syamimi Mardiah, Shaharum; Yasmin, Abdul Wahab; Muhammad Hazarul Azmeer, Ab Malek; Mohamad Shaiful, Abdul Karim; Nurhafizah, Abu Talip Yusof (Kyushu University, 2024)
This paper presents a substrate-integrated waveguide (SIW) antenna designed for K-band and Ka-band applications, addressing propagation and radiation losses at higher frequencies. The proposed patch antenna integrates SIW principles with copper vias and three-ring slots, enhancing the radiation pattern’s bandwidth, gain, and stability. Optimized using Computer Simulation Technology (CST) software on a Rogers RT/duroid 5880 substrate (εr = 2.2, thickness = 1.575 mm), results in the SIW triple-ring slot patch antenna (SIW-PS3) exhibiting triple-band resonance at 26.066 GHz, 31.552 GHz, and 33.54 GHz, with matching coefficients of -31.96 dB, -47.72 dB, and -21.97 dB, respectively. The SIW-PS3 demonstrates superior performance, including a 9.91% impedance bandwidth (24.826-27.258 GHz), peak gain of 8.072 dB at 26.066 GHz, maximum radiation efficiency of 93%, VSWR between 1 and 5, and directivity ranging from 8.12 to 10.2 dB. These features make it particularly suitable for diverse K-band and Ka-band applications.